2004
DOI: 10.1292/jvms.66.1027
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Induced Hyperactivation of Canine Spermatozoa Associated with Disappearance of Lectin-Binding Glycoproteins on their Surface

Abstract: ABSTRACT. The relationship between the disappearance of glycoproteins from the surface of canine sperm and sperm capacitation was investigated in vitro. The protease (PR) concentration in flush fluids of the uterine horns and oviducts removed from 6 estrous, 5 diestrous, and 5 anestrous bitches was measured with a protease assay kit. Ejaculated sperm collected from 10 dogs were incubated for 4 hr in Eagle's MEM supplemented with 1 or 5 µg/ml PR, or to which no PR had been added (control). The glycoproteins on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Protease activity has been reported in oviducts in several species, and some of their functions have been linked to sperm capacitation [ 68 , 69 ]. We identified 27 proteases and 16 protease inhibitors expressed by oviductal cells ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Protease activity has been reported in oviducts in several species, and some of their functions have been linked to sperm capacitation [ 68 , 69 ]. We identified 27 proteases and 16 protease inhibitors expressed by oviductal cells ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although proteases have been implicated in the reproduction, only a few are associated with the process of capacitation (Zheng et al 2001, Kawakami et al 2004. As for serine protease inhibitors, there also seem few reports to point out the direct action on the process of sperm capacitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amino acid sequence of the PSA published by Watt et al (1986) is not in complete agreement with the results inferred from the cDNA sequence, such differences have been suggested to be due to allelic variations (Lundwall et al 2006). The predominant canine protease from seminal fl uid (Kawakami et al 2004) has also been suggested to be a possible member of the glandular kallikrein family, based on its partial amino acid sequence data (Lazure et al 1984).…”
Section: Introductionmentioning
confidence: 94%